If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 7x + -5 Reorder the terms: 9 + 3x = 7x + -5 Reorder the terms: 9 + 3x = -5 + 7x Solving 9 + 3x = -5 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + 3x + -7x = -5 + 7x + -7x Combine like terms: 3x + -7x = -4x 9 + -4x = -5 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + -4x = -5 + 0 9 + -4x = -5 Add '-9' to each side of the equation. 9 + -9 + -4x = -5 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = -5 + -9 -4x = -5 + -9 Combine like terms: -5 + -9 = -14 -4x = -14 Divide each side by '-4'. x = 3.5 Simplifying x = 3.5
| 122=9/5c+32 | | 4w+12(w-1)=36 | | 2(x+5)+3(x-5)=180 | | -5b=-8 | | 4x^2+8x=320 | | 21d-4=-67 | | -5(2t-3)+2t=8t-6 | | 8-2x+8+1=5x+5+1 | | 3*x-4=11 | | 3(4y-21)=7 | | 0.25x+7=0.33x-8 | | loge(x^2)-2=0 | | -2xy=-3 | | 15-.75z=13-.50z | | -6+3v+v=6 | | r+26-32r=-41 | | 8x^2-16x-8=0 | | -3(4t-5)+2t=6t-4 | | 2x+[5x(-2x-3x)]= | | 6x-10=2x-2 | | X=4x+8x | | 11-4n=17 | | 3x=11+49 | | 10=h-5g | | 2.2-7.3= | | 3t+5=3(5+t) | | 15-.75z=13.50z | | 2(5-2x)=15.1-7x | | -7r-39r=115 | | 7(7x-7)=-196 | | 180-(5x-10)=8x-5 | | z-9z=4z-5-z |